Thrombomodulin induces anti-inflammatory effects by inhibiting the rolling adhesion of leukocytes in vivo - Shino Nishizawa; Junichi Kikuta; Shigeto Seno; Masahiro Kajiki; Ryuichi Tsujita; Hiroki Mizuno; Takao Sudo; Tomoka Ao; Hideo Matsuda; Masaru Ishii (Elsevier, 2020)
Thrombomodulin (TM) is an integral membrane protein expressed on the surface of vascular endothelial cells that suppresses blood coagulation. Recent studies have shown that TM exhibits anti-inflammatory effects by inhibiting leukocyte recruitment. However, the actual modes of action of TM in vivo remain unclear. Here, we describe the pharmacological effects of recombinant human soluble TM (TM alfa) on leukocyte dynamics in living mice using intravital imaging techniques. Under control conditions, neutrophils exhibited three distinct types of adhesion behavior in vessels: 1) "non-adhesion", in which cells flowed without vessel adhesion; 2) "rolling adhesion", in which cells transiently interacted with the endothelium; and 3) "tight binding", in which cells bound strongly to the endothelial cells. Compared to control conditions, local lipopolysaccharide stimulation resulted in an increased frequency of rolling adhesion that was not homogeneously distributed on vessel walls but occurred at specific endothelial sites. Under inflammatory conditions, TM alfa, particularly the D1 domain which is a lectin-like region of TM, significantly decreased the frequency of rolling adhesion, but did not influence the number of tight bindings. This was the first study to demonstrate that TM alfa exerts anti-inflammatory effects by inhibiting rolling adhesion of neutrophils to vascular endothelial cells in living mice. Keywords: Thrombomodulin, Rolling adhesion, Leukocyte, Endothelial cell, Intravital imaging